2014
DOI: 10.1002/smj.2275
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and IPO underpricing in a cross‐national sample: A multilevel knowledge‐based view

Abstract: Prior studies of IPO underpricing, mostly using agency theory and single-country samples, have generally fallen short. In this study, we employ the knowledge-based view (KBV) to explore underpricing across 17 countries. We find that agency indicators are insignificant predictors, that board of director knowledge limits underpricing, and external knowledge both substitutes for and complements internal board knowledge. This third finding suggests that future KBV studies should consider how internal and external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 64 publications
(74 reference statements)
2
47
0
2
Order By: Relevance
“…The list of IPOs is selected from the EURIPO database, which has been used in previous IPO studies (e.g. Chambers and Dimson, 2009;Judge et al, 2015b;Vismara, Paleari and Ritter, 2012). To guarantee comparability of corporate governance features, we also excluded IPOs of foreign firms in the German stock market.…”
Section: Sample and Datamentioning
confidence: 99%
“…The list of IPOs is selected from the EURIPO database, which has been used in previous IPO studies (e.g. Chambers and Dimson, 2009;Judge et al, 2015b;Vismara, Paleari and Ritter, 2012). To guarantee comparability of corporate governance features, we also excluded IPOs of foreign firms in the German stock market.…”
Section: Sample and Datamentioning
confidence: 99%
“…Also, all of the firms in the sample are approved by the CSRC to go public, so there might be a potential sample selection bias that presents an interesting topic for future study. Recently, there has been growing interest examining IPO from a cross‐country viewpoint (Judge et al, ). Admittedly, some of the results of our research may be idiosyncratic to China and to its particular minority ownership mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, CEOs of entrepreneurial ventures oftentimes lack these characteristics because their careers tend to have been developed in small private companies (Certo, Covin, Daily, & Dalton, ). Investors therefore also pay particular attention to the board as a potential resource signal in terms of the advice it provides to the CEO in the decision‐making process, thus increasing the initial market valuation of the IPO firm (Chahine et al, ; Judge et al, ; Sundaramurthy et al, ). Specifically, prior research has suggested that the competences, skills, and relationships that the board acquires through prior experiences are good signals of an effective resource provision role of the board at the IPO stage as they are assumed to facilitate access to external resources and provide strategic advice to the managers (Arthurs, Busenitz, Hoskisson, & Johson, ; Sundaramurthy et al, ; Walters, Kroll, & Wright, ).…”
Section: Introductionmentioning
confidence: 99%
“…A costly and easily observable signal that can enhance firm value at IPO is that the firm has solid leadership, represented by the CEO (Yang, Zimmerman, & Jiang, 2011). Investors likely value CEOs with negotiating skills and knowledge about public markets that could support the firm in successfully making and developing the newly required strategies (Judge et al, 2015). Yet, CEOs of entrepreneurial ventures oftentimes lack these characteristics because their careers tend to have been developed in small private companies (Certo, Covin, Daily, & Dalton, 2001).…”
Section: Introductionmentioning
confidence: 99%